A Proteomic Study Based on Home Quarantine Model Identifies NQO1 and Inflammation Pathways Involved in Adenoid Hypertrophy - Chen P; Hou S; Pang X; Li L; Wei W (Journal of Inflammation Research)
Penghui Chen,1– 3,* Shule Hou,1– 3,* Xiuhong Pang,4 Lei Li,1– 3 Wei Wei1– 3 1Department of Otorhinolaryngology-Head and Neck Surgery, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Ear Institute, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 3Shanghai Key Laboratory of Translational Medicine on Ear and Nose Diseases, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 4Department of Otolaryngology-Head and Neck Surgery, the Affiliated Taizhou People’s Hospital of Nanjing Medical University, Taizhou School of Clinical Medicine, Nanjing Medical University, Taizhou, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Wei; Lei Li, Department of Otolaryngology-Head & Neck Surgery, Xinhua Hospital affiliated to Shanghai Jiao Tong University School of Medicine, 1665 Kongjiang Road, Yangpu District, Shanghai, 200082, People’s Republic of China, Tel +86-21-25078893, Fax +86-21-65152394, Email weiwei8319@xinhuamed.com.cn; xyyh2711@126.comBackground: Adenoid hypertrophy is a common disorder of childhood, and has an unclear pathogenesis. At the beginning of the COVID-19 pandemic, there was a significant reduction in the incidence of adenoid hypertrophy in children under long-term home quarantine, providing a rare research model to explore the pathogenesis and treatment targets of adenoidal hypertrophy in children.Methodology: Before and during the home quarantine period, adenoids that underwent surgery were detected using label-free proteomics. Differences in protein expression were analyzed using Gene Ontology, the Kyoto Encyclopedia of Genes and Genomes, Gene Set Enrichment Analysis, Protein-protein interaction, and immunohistochemistry analysis.Results: Long-term home quarantine had a profound impact on the proteomics of pediatric adenoids, with up-regulated and down-regulated proteins of 28 and 92 downregulated proteins, respectively. Functional enrichment analysis showed that the differentially expressed proteins were mainly enriched in pathways such as leukocyte activation, inflammatory response, IL-1 production, Th17 cell differentiation, and IL-17 signaling. In the home quarantine group, inflammation-related proteins (TNF-α, IL-6), CD36, and S100A2, were considerably reduced, whereas NQO1 levels increased significantly, potentially alleviating adenoid hypertrophy. NQO1, CD36, NDUFS8, and NDUFAF2 exhibited strong interactions.Conclusion: This study identified some candidate differential proteins, such as NQO1, CD36, S100A2, and the inflammation pathways involved in adenoid hypertrophy in preschool children.Keywords: COVID-19, home quarantine, adenoidal hypertrophy, proteomics, NQO1